1994
DOI: 10.1017/s0001924000049745
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of Euler equations for aerofoils in arbitrary unsteady motion

Abstract: This paper is part of a DLR research programme to develop a three-dimensional Euler code for the calculation of unsteady flow fields around helicopter rotors in forward flight. The present research provides a code for the solution of Euler equations around aerofoils in arbitrary unsteady motion. The aerofoil is considered rigid in motion, and an O-grid system fixed to the moving aerofoil is generated once for all flow cases. Jameson's finite volume method using Runge-Kutta time stepping schemes to solve Euler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There is a trend of underprediction that has also be seen by several other researchers. 36,[41][42][43][44][45] Now, considering the relative motion simulation, there is good agreement compared to the ALE approach, with the largest deviations occurring at the maximum pitch up and pitch down conditions. The normal force coefficient curve for the relative motion case also produces slightly more noise as a result of the computational surface mesh constantly changing as the airfoil sweeps through the stationary Cartesian mesh.…”
Section: Iiic Oscillating Naca 0012 Airfoilmentioning
confidence: 99%
“…There is a trend of underprediction that has also be seen by several other researchers. 36,[41][42][43][44][45] Now, considering the relative motion simulation, there is good agreement compared to the ALE approach, with the largest deviations occurring at the maximum pitch up and pitch down conditions. The normal force coefficient curve for the relative motion case also produces slightly more noise as a result of the computational surface mesh constantly changing as the airfoil sweeps through the stationary Cartesian mesh.…”
Section: Iiic Oscillating Naca 0012 Airfoilmentioning
confidence: 99%
“…The second test case is that suggested by Lerat and Sides [10] for in-plane motion. Calculations were performed for a NACA 0012 aerofoil undergoing a motion described by equation (12) with r=Rˆ0:892, M tipˆ0 :60, í rˆ0 :61 and k rˆ0 :185. The angle of incidence and Reynolds number based upon chord were áˆ08 and Re c1…”
Section: In-plane Motionmentioning
confidence: 99%
“…Habibie et al [11] investigated the aerodynamics of aerofoils subjected to harmonic variations of Mach number and ramping motions (dM=dtˆconstant). Subsequently, Pahlke et al [12,13] compared solutions of the two-and three-dimensional Euler equations at conditions representative of helicopter rotors at various forward flight speeds. These calculations suggest that, for the geometry considered, three-dimensional effects are significant.…”
mentioning
confidence: 99%
“…Qin and Richards" 8 - 19 > compared a sparse finite-difference Newton method with a sparse quasi-Newton method for the solution of the Navier-Stokes equations and concluded that, while the former can demonstrate a quadratic convergence, the latter can be more efficient as the approximate Jacobian is updated rather than calculated. Instead of calculating the Jacobian using finite difference, Badcock and Richards' 2 '" followed an approach to derive the analytical Jacobian using the chain rule to obtain the following expression _3E___3E_ d^dQ^ ... (10) 3Qi " 3Qi + 3Q, 9Q, Here 9E/3Q () and 3E/3Q, are the Jacobians of the flux vector with respect to the left and right states used in the approximate Riemann solver. The remaining terms dQ ( /3Qj and dQi/8Qj arise from the MUSCL interpolation of the primitive variables and were obtained using a symbolic manipulation package, REDUCE.…”
Section: Derivation Of the Flux Jacobianmentioning
confidence: 99%
“…32 flux evaluations are required (this is equivalent to 16 right hand side calculations) for second order accuracy of the Jacobian terms together with a small overhead for the calculation of the terms arising from the interpola-tion procedure. Further improvements in computational efficiency can be obtained by using analytical expressions to evaluate all of the terms on the right hand side of Equation (10). The complicated nature of the numerical fluxes arising from Osher's scheme has dissuaded most authors from deriving analytical expressions for the flux Jacobians directly.…”
Section: Derivation Of the Flux Jacobianmentioning
confidence: 99%